2005
DOI: 10.1890/04-1588
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs Related to Ecosystem Engineering: A Case Study on Stiffness of Emerging Macrophytes

Abstract: Abstract. Biologically mediated modifications of the abiotic environment, also called ecosystem engineering, can significantly affect a broad range of ecosystems. Nevertheless, remarkably little work has focused on the costs and benefits that ecosystem engineers obtain from traits that underlie their ecosystem engineering capacity. We addressed this topic by comparing two autogenic engineers, which vary in the degree in which they affect their abiotic environment via their physical structure. That is, we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
404
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(456 citation statements)
references
References 70 publications
17
404
3
Order By: Relevance
“…Hydrodynamic traits were measured in a unidirectional flow flume (full description in Bouma et al, 2005). The width of the straight working section of the flume was 30 cm and the height of the water column was 25 cm.…”
Section: Drag Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamic traits were measured in a unidirectional flow flume (full description in Bouma et al, 2005). The width of the straight working section of the flume was 30 cm and the height of the water column was 25 cm.…”
Section: Drag Measurementsmentioning
confidence: 99%
“…The width of the straight working section of the flume was 30 cm and the height of the water column was 25 cm. Drag was measured using a force transducer (WL|Delft Hydraulics, Delft, the Netherlands, described in Bouma et al, 2005). A hole fitting the size of the transducer was made in the bottom of the flume so that the transducer was placed underneath with its top part perfectly level with the bottom of the flume.…”
Section: Drag Measurementsmentioning
confidence: 99%
“…Furthermore, remaining salt marshes are at risk of drowning (Roman et al 1997;Reed 2002) as a result of global sea-level rise (Douglas et al 2001) and a local reduction in (riverine) sediment supply (Yang et al 2006). The ability of salt marshes to accrete in response to sea-level rise by trapping sediment is strongly dependent on the attenuation of waves and currents (Friedrichs and Perry 2001;Leonard and Reed 2002;Bouma et al 2005a). Hence, from the perspective of both coastal defense and salt marsh management, an in-depth understanding is needed of the way in which waves are attenuated by salt marshes.…”
Section: Introductionmentioning
confidence: 99%
“…Flume experiments have shown that wave damping by salt marshes is strongly affected by vegetation characteristics (e.g., Bouma et al 2005aBouma et al , 2010. Flumes are, however, of limited use for studying the effect of flooding height on wave attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…29,31], but also by the height [32], stem diameters and configuration of the branches and leaves. For example, dissipation was roughly three times higher in vegetation with stiff leaves than in vegetation with flexible leaves [33]. Therefore, some saltmarsh plant species are more effective in wave damping than others.…”
Section: Effect Of Natural Forelands On the Probability Of Floodingmentioning
confidence: 99%